Prevalence of metal fume fever and its association with working conditions and chronic respiratory disorders among metal factory workers in eastern India - Nawal, Harsh; Mohta, Sakshi; Sarkar, Suhena; Paramita Pal Bhattacharyya; Biswas, Birupaksha (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Metal fume fever (MFF) constitutes a formidable occupational infirmity, arising from inhalation of ultrafine metallic particulates, pre-eminently zinc oxide, during metallurgical vocations. It’s symptomatology, characterized by pyrexia, bronchospasm, and the recurrent “Monday morning” febrile paroxysm, conceals a sinister trajectory toward chronic respiratory decline. Methods: A cross-sectional epidemiological inquiry was conducted among 181 metallurgical operatives in Liluah, West Bengal (July-December 2024). Participants, conscripted via multi-stage randomization, were interrogated using a validated questionnaire encompassing socio-demographic indices, occupational exposures, and respiratory morbidities. Analytical dissections employed ANOVA, chi-square, Z-tests, and Pearson correlations via SPSS v20, consecrating significance at p≤0.05. Results: MFF prevalence attained an alarming 87.8%, with mean recurrence of 5.91±4.58 episodes annually. Nearly half (49.7%) harboured chronic respiratory disorders: COPD (24.3%), chronic bronchitis (17.7%), and asthma (7.7%). Robust associations emerged between MFF occurrence and sex (χ2=62.242, p<0.001), literacy (χ2=50.752, p<0.001), smoking (χ2=65.615, p<0.001), alcohol use, PPE compliance, ventilation, shift schedule, and primary metal exposure. Frequency of MFF episodes correlated near-perfectly with age (r=0.911), occupational tenure (r=0.928), daily working hours (r=0.838), cigarette consumption (r=0.952), and smoking duration (r=0.973). Conclusions: Metal fume fever demonstrates an exceptionally high prevalence among metallurgical workers, acting as a sentinel for chronic respiratory morbidity. The strong correlations with occupational exposures and lifestyle factors underscore its preventable nature. Implementation of protective strategies and worker education is imperative to mitigate long-term pulmonary damage.